Targeting HSP90 in ovarian cancers with multiple receptor tyrosine kinase coactivation - Zhou Haimeng; Meng Fanguo; Ou Wenbin; Jiao Yisheng; Wang Aiyuan (Molecular Cancer, 2011)
Abstract Background Ovarian cancer has the highest mortality rate of all gynecologic malignancy. The receptor tyrosine kinases (RTKs), including EGFR, ERBB2, PDGFR, VEGFR and MET, are activated in subsets of ovarian cancer, suggesting that these kinases might represent novel therapeutic targets. However, clinical trials have not or just partially shown benefit to ovarian cancers treated with EGFR, ERBB2, or PDGFR inhibitors. Despite multiple RTK activation in ovarian cancer pathogenesis, it is unclear whether transforming activity is dependent on an individual kinase oncoprotein or the coordinated activity of multiple kinases. We hypothesized that a coordinated network of multi-RTK activation is important for the tumorigenesis of ovarian cancers. Results Herein, we demonstrate co-activation of multiple RTKs (EGFR, ERBB2, ERBB4, MET and/or AXL) in individual ovarian cancer cell lines and primary tumors. We also show that coordinate inhibition of this multi-kinase signaling has substantially greater effect on ovarian cancer proliferation and survival, compared to inhibition of individual activated kinases. The inhibition of this multi-RTK signaling by HSP90 suppression results in profound pro-apoptotic and anti-proliferative effects, and is associated with the inactivation of RTK downstream PI3-K/AKT/mTOR and RAF/MAPK signaling. Conclusion These studies suggest that anti-multiple RTK strategy could be useful in the treatment of ovarian cancer.